IMPLEMENTASI PRINSIP WADIAH PADA BANK SAMPAH SYARIAH MANDIRI SUMRINGAH NGAMPELSARI KECAMATAN CANDI KABUPATEN SIDOARJO - ika karlina (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2019)
ABSTRACTThis study aims to provide a description of the Implementation of the â€œSumringahâ€ independent sharia Â waste bank in Ngampelsari Village, Candi District, Sidoarjo Regency. At the same time to explain that the â€œSumringahâ€ independent sharia Â waste bank is in accordance with the Wadiah Principles.This research uses qualitative research methods with data analysis using descriptive data analysis to describe the reality of the implementation of the wadiah contract in the implementation of the "Syariah Mandiri" Waste Bank in Ngampelsari Village, Candi District, Sidoarjo Regency.The implementation of the Mandiri Syariah Waste Bank is according to the Management of the Waste Bank. Also according to the Law and Regulations nowdays. â€œSumringahâ€ independent sharia Â waste bank is according to the Standard of waste bank managements. And if viewed from the Application of Wadiah Principles related to the Implementation of â€œSumringahâ€ independent sharia Â waste bank, it has fulfilled the elements contained in the wadiah provisions. Such as, there is a statement to bind oneself, there are parties who are mindful and there is an object of contract. In the work mechanism of the independent sharia garbage bank, it is already offering (ijab) and acceptance (qabul), there are parties who contract, can use the original guardian who qualifies to be a representative. The wadi'ah object in the independent sharia waste bank is also clear and well-known by its owners and depositors.The assets that are deposited are also prices that can be physically owned. Such as the money from the sale of garbage. Perpetrators in independent sharia waste banks are also capable of law, baligh and are able to keep and maintain safe keeping. However, there are things that need to be considered in the application of this Wadia principle, such as the transparency on the agreement sheet that the parties agree to bind themselves in the wadiah contract as outlined in writing. In order to the Customer knows that the Customer Savings is related to the Wadiah contract.Â Keywords : Wadiah, Islamic Waste Bank